A prospective study of maternal and fetal outcome in patients with hypertensive disorders of pregnancy and COVID-19 infection in a tertiary care center - Chavan, Niranjan; Simpatwar, Sonam; Kapote, Deepali; Deshmukh, Prasad; Sakhalkar, Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: During the current COVID-19 epidemic, managing pregnant patients is an issue. Pregnant women with coronavirus infection have an increased risk of miscarriage, preclampsia, caesarean delivery, and neonatal mortality. The additive effect of COVID-19 infection and preclampsia in pregnancy may affect the fetal and maternal outcome in a more complicated way. There have been only a few studies till now to observe the combined effect of both in pregnancy. Our study aims to observe and analyse the maternal and fetal outcomes in pregnancy complicated by preclampsia and COVID-19 infection. Methods: This is a prospective study at a tertiary referral facility. This research included women with hypertension who were hospitalized for delivery and screened for SARS-RTPCR using a nasopharyngeal swab from April 2020 to September 30, 2021. The maternal and neonatal outcomes were studied and analyzed. Results: In our study of 65 women with COVID-19 infection and hypertensive disorders in pregnancy, about 6 (9.2%) had eclampsia, 6 (9.2%) had abruptio placenta, 5 (7.6%) had DIC, 3 (4.6%) had HELLP, 2 (3.07%) had acute kidney injury, 2 (3.07%) had ARDS, and 1 (1.5%) had PRESS. 4 (6.1%) had chronic hypertension. Further, 12 (18.4%) of patients needed ICU admission with ventilatory support; about 5 (7.6%) was the rate of maternal deaths in our study. 43 (65%) of neonates were appropriate for gestational age, while 20 (32%) were low birth weight and 2 (3%) were extremely low birth weight. 45% of women with preclampsia develop complications. Conclusions: Our study concluded that complications from preclampsia are more common in women with COVID-19 infection, but a larger sample size is necessary for statistical significance.